Effect Enrichment Daphnia sp . Viterna With Survival and Growth of Catfish Larvae baung (Hemibagrus nemurus) - Erwin '; Nuraini '; Sukendi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The research was conducted from January to March 2016 at No. 38 Panam . This study aims to determine the survival and growth of the best in fish larvae baung ( Hemibagrus nemurus ) by feeding Daphnia sp . enriched with VITERNA . The method used in this study is an experimental method , while the design used was completely randomized design ( CRD ) with two- level factorial treatments and two replications . By immersion 3 hours and 5 hours. P0 ( control ) , P₁ ( I Enrichment viterna with a dose of 20 ml / l ) , P₂ (Enrichment viterna with a dose of 30 ml / l ) , P₃ (Enrichment viterna with a dose of 40 ml / l ) . Growth highest in absolute weight soaking 5 hours at a dose of 30 ml / l ie 0498 g . Length growth the absolute highest in soaking 5 hours at a dose of 40 ml / l which is 2,655 cm , while the daily growth rate is highest in the soaking 5 hours at a dose of 30 ml / l which is 6365 % , and the rate of survival is highest in the immersion 3 hours at 20 doses of 100 % .Keywords: Hemibagrus nemurus,viterna , growth, and survival